2005
DOI: 10.1080/09500340512331323457
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in the presence of metallic hole arrays

Abstract: We show that the transmission of light through metallic hole arrays supported by a glass substrate can be tuned by depositing a controlled number of LangmuirBlodgett layers on top of the hole array. Enhanced transmission is achieved when the number of overlayers is such that the surface plasmon-polariton modes on the two sides of the metal hole array have matched wavevectors. Dye molecules introduced into some of these overlayers allow us to explore the relationship between molecular fluorescence and the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The top-down, unconventional lithographic techniques described above are particularly interesting for the fabrication of nanoplasmonics systems (i.e., metal nanoantennas and nanohole (NH) arrays) [29][30][31][32][33]. In particular, metallic NH arrays are being widely studied to get a basic understanding and optimization of their optical, as well as their applications in several fields (for instance, sub-wavelength photolithography [34,35], nonlinear optics (interferometric plasmonic lensing) [36,37], surface-enhanced Raman scattering (SERS) [38,39], surface-enhanced fluorescence spectroscopy [40][41][42], and especially as chemical sensors and biosensors [28,[43][44][45][46][47]).…”
Section: Introductionmentioning
confidence: 99%
“…The top-down, unconventional lithographic techniques described above are particularly interesting for the fabrication of nanoplasmonics systems (i.e., metal nanoantennas and nanohole (NH) arrays) [29][30][31][32][33]. In particular, metallic NH arrays are being widely studied to get a basic understanding and optimization of their optical, as well as their applications in several fields (for instance, sub-wavelength photolithography [34,35], nonlinear optics (interferometric plasmonic lensing) [36,37], surface-enhanced Raman scattering (SERS) [38,39], surface-enhanced fluorescence spectroscopy [40][41][42], and especially as chemical sensors and biosensors [28,[43][44][45][46][47]).…”
Section: Introductionmentioning
confidence: 99%
“…It has already been shown that enhanced light transmission could be achieved through a subwavelength array of cylindrical holes in metallic films [1][2][3][4]. This type of nanostructure offers many interesting applications: nanophotonics [5,6], nanophotolithography [7,8], fluorescence [9,10] and chemical sensors [11]. In order to increase the transmission, Baida and Van Labeke recently proposed a structure which consists of an array of nanometric coaxial cavities in a real metal (gold for instance) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The EM field enhancement can be even greater in a nanostructure where the light is efficiently confined at the subwavelength holes. Such enhancement has allowed potential application in many different areas, such as sensing [3], integrated nano/microphotonics [4], plasmonic photolithography [5], fluorescence microscopy [6], surface enhanced Raman scattering (SERS) [7], second harmonic generation (SGH) [8], and supercontinuum generation (SCG) [9].…”
Section: Introductionmentioning
confidence: 99%